EDUCATION POLICY AN D GLOBAL IZATION:&NBSP;NATIONAL AND SUPRANATIONAL PECULARITIES - Duoblienė, Lilija (Acta Paedagogica Vilnensia, 2010)
The article analysis the problem of national education policy in the contexts of globalization, searching for the answer how much power has the state to protect national interests and to stand against the process of globalization, if is possible to combine national and supranational education policy and what is consequences of it for national education. Different points of view toward the influence of international organizations on national education, emphasizing their interest are analyzed, and then different educational ideologies in compliance with globalization and possibilities to ensure social equity are investigated. This analysis is linked with Lithuanian situation, trying to find out the symptomatic of Lithuanian education policy. The article summarizes that Lithuanian education policy for many years had not clear direction and had balanced between national and international interests. Recently the direction is more obvious, but still eclectic, because it stresses the policy based on liberal education, though declares strategies toward conservative education for the strong state and at the same time claims neomarxist statements toward the restruction of the society.